Psychoanalytic insights into social, political, and organizational dynamics : understanding the age of Trump - Allcorn, Seth; Stein, Howard F. (New York, NY : Routledge, 2022)
"This fascinating interdisciplinary work explores US politics since 2015 and offers psychodynamic insights into the unconscious undercurrents of contemporary culture and politics in the United States. Allcorn and Stein expertly lead readers up the steep learning curve of understanding the Trump era by exploring seven key elements of recent political dynamics. Using the complementary psychodynamic models of object relations, group relations and Karen Horney's tripartite theory, this book makes sense of the Age of Trump and its chaotic world of alternate facts, conspiracy theories, reality TV politics, hoax pandemics, and the sweeping chaos of life in the US. This sense-making relies on two triangulations. The first represents the complex systemic political scene. The second uses three psychoanalytic theories to understand social, political, and organizational dynamics. This book is a key resource for helping readers know and understand ourselves, our fellow citizens, colleagues, family, friends and what Trump and his followers call "them" such as liberals and foreign immigrants, as well as both the larger polarized social and political context in the United States today. The book also provides concrete examples of how these discoveries can be operationalized both in organizations and at the level of national government and leadership. This book is an essential reading for students in organizational behavior including leadership and how governments operate, as well as behavioral health professionals consulting or offering therapy to organizations"--
Keywords: Trump, Donald, -- 1946-; Political culture -- United States -- History -- 21st century; Conspiracy theories -- United States -- History -- 21st century; Fake news -- United States -- History -- 21st century; United States -- Politics and government -- 21st century; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Organizational Behavior; POLITICAL SCIENCE / Political Process / Leadership